2002
DOI: 10.1046/j.1365-4362.2002.01463.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid initiation of repigmentation in vitiligo with Dead Sea climatotherapy in combination with pseudocatalase (PC‐KUS)

Abstract: The results of this study show a significantly faster initiation of repigmentation in vitiligo after a combination of short-term climatotherapy (21 days) at the Dead Sea in combination with a pseudocatalase cream (PC-KUS) compared to either conventional climatotherapy at the Dead Sea alone or with placebo cream in combination with climatotherapy. This combined therapy is significantly faster in repigmentation than narrowband UVB activated pseudocatalase cream (PC-KUS) treatment alone. The results of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 31 publications
1
61
0
4
Order By: Relevance
“…Removal of H 2 O 2 by antioxidant has been proven to be beneficial to patients. Several reports suggested that a topical substitution with a UVB-activated pseudocatalase can successfully remove epidermal H 2 O 2 and achieve remarkable repigmentation in vitiligo (13,14). In contrast, other researchers found that topical pseudocatalase was not effective for vitiligo in an open, single-center study (15).…”
Section: Introductionmentioning
confidence: 99%
“…Removal of H 2 O 2 by antioxidant has been proven to be beneficial to patients. Several reports suggested that a topical substitution with a UVB-activated pseudocatalase can successfully remove epidermal H 2 O 2 and achieve remarkable repigmentation in vitiligo (13,14). In contrast, other researchers found that topical pseudocatalase was not effective for vitiligo in an open, single-center study (15).…”
Section: Introductionmentioning
confidence: 99%
“…The basis for the use of this agent in vitiligo is the evidence of oxidative stress and high H 2 O 2 levels in the lesional skin 37 . While some earlier studies demonstrated excellent results with this agent in inducing repigmentation in vitiligo, later studies have cast doubts on its efficacy 38 .…”
Section: Pseudocatalasementioning
confidence: 99%
“…A rather uncommon, but effective, treatment modality is the combination of pseudocatalase and balneo/climatotherapy at the Dead sea (Krϋger et al, 2011; as cited in Schallreuter et al, 2002). Krϋger and colleagues showed in their study that group therapy had a strong and long-lasting positive effects in quality of life in vitiligo patients (Krϋger et al, 2011).…”
Section: Other Complementary Modalitiesmentioning
confidence: 99%